Moments of meeting: A case study of Shared Reading of poetry in a care home - Tangerås, Thor Magnus (Frontiers in Psychology, 2022)
Abstract There is a growing research interest in the value of participative arts-based strategies for enhancing well-being amongst adults living with dementia. One such intervention, centred around literature, is the group activity called Shared Reading. The purpose of this case study of weekly shared reading sessions of poetry in a care home in Merseyside is to investigate instances of how participants with mild to moderate dementia collaborate in processes of meaning-making that allow them shared experiences of being moved by poetry. An under-thematised aspect of psychological well-being is the capacity for being moved and for sharing such moments. This article addresses the following question: how can the specific multimodality of the text (participants have a copy of the text before them, the poem is read aloud and there may be use of non-verbal aids) in the Shared Reading model help to bring about such experiences? Using Stern’s concepts of Now Moments and Moments of Meeting, this case study discusses various instances of unpredictable, surprising and spontaneous intersubjective moments between participant and poem, participant and reader leader, participant and staff, participant and relative.